VARIETIES OF ADAPTATION IN THE INSECT WORLD - Akhmedova Mastura Makhmudovna; Abdikodirova Ogloy Adkhamjan's daughter (Academia Science Repository, 2023)
Adaptations are an example of an idioadaptive direction of evolution, through which organisms strive to win the struggle for survival. This article discusses the process of adaptation in the insect world, its varieties, the role of adaptation in insect life.